SpO2 and PetСО2 signal analysis in closed-loop mechanical lung ventilation systems - Bodilovskyi, Oleg; Popov, Anton; Zakorchevnyi, Mykhailo (Видавництво Львівської політехніки, 2012)
Employment of SpO2 and PetСО2 signal analysis for setting parameters of mechanical lung ventilation in closed-loop systems is considered. Results of time-frequency representation of such signals are presented and discussed.
Keywords: SpO2 analysis; PetСО2 analysis; closed-loop mechanical lung ventilation